The Deceiving Mirror. Altered Body Perception and Alexithymia in a Group of Sports Adolescents and Adults. Issue 7 (3rd October 2019) - Iacolino, Calogero; Pellerone, Monica; Mannino, Giuseppe; Lombardo, Ester Maria Concetta; Pasqualetto, Elisabetta Rita; Formica, Ivan
Abstract : Recent literature emphasizes an altered perception of the body in subjects practicing sport to pursue an ideal body image. Sometimes such bodily misperception is associated with the inability to recognize and express emotions, and addiction to sport. This research investigates the relationship between body image and alexithymia in a group of 363 sportive adolescents and adults, including 78 males and 285 females, aged 11 to 68 years. Participants completed the Anamnestic Data Questionnaire, Body Uneasseness Test, and Toronto Alexithymia Scale (TAS-20). Results highlight differences between adolescents and adults, especially about externally oriented thinking, concern for body image, and compulsive self-monitoring.